INTERGOVERNMENTAL RELATIONS DALAM PENANGANGAN COVID-19 DI KOTA PEKANBARU TAHUN 2020 - Hidayat, Taufik; Marta, Auradian (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The study was conducted in 2020 in Pekanbaru City, Riau Province, Pekanbaru City was faced with health problems, namely the spread of COVID-19 cases, in handling COVID-19 in Pekanbaru City with the implementation of PSBB in Pekanbaru City followed up by Riau Province in the Riau Governor's decision Number: Kpts. 1351/IX/2020 concerning the Formation of the Task Force for the Acceleration of Handling COVID-19 and the City of Pekanbaru in the Decree of the Mayor of Pekanbaru Number: 284 of 2020 concerning the Formation of the Task Force for the Acceleration of Handling COVID-19 in the City of Pekanbaru. The purpose of this study is to find out how the Intergovernmental Relations and Intergovernmental Relations Model of the Pekanbaru City government in handling the spread of COVID-19.The approach used in this study is a qualitative approach. This type of research is descriptive. This research is located in Pekanbaru City. The type of data in this study is divided into primary data and secondary data. Data collection techniques using interviews, observations and documentation as well as data analysis techniques in this study were qualitative.The results of the research obtained by the author of coordination and cooperation between Pekanbaru City and Riau Province did not go well and the lack of coordination and cooperation between Pekanbaru City government agencies and the Riau Province Government. The findings of the research conducted by the authors in the field of intergovernmental relations between the Pekanbaru City Government and the Riau Provincial Government were not going well due to weak coordination and cooperation, as well as the intergovernmental relations model that occurred, namely an imperfect government relationship model or a pseudo inclusive authority where the relationship between the Pekanbaru City government and Riau Province (Pekanbaru City government as implementer in Pekanbaru City and Riau Provincial Government as director in Riau Province) in carrying out PSBB in handling COVID-19.Â Â Kata Kunci: Intergovernmental Relations, Handling COVID-19.